2022
DOI: 10.1186/s41021-022-00237-2
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol phosphate as a photosensitizer in the reaction of nucleosides with UV light: formation of 5,6-dihydrothymidine

Abstract: Introduction α-Tocopherol phosphate, a natural water-soluble α-tocopherol analog, exists in biological tissues and fluids. Synthesized α-tocopherol phosphate is used as an ingredient of cosmetics. Findings When a neutral mixed solution of 2′-deoxycytidine, 2′-deoxyguanosine, thymidine, and 2′-deoxyadenosine was irradiated with UV light at wavelengths longer than 300 nm in the presence of α-tocopherol phosphate, thymidine was markedly consumed in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…(14) Recently, we reported that α-tocopherol phosphate induces the UV reaction of nucleosides, especially dT, generating 5,6dihydrothymidine as the major product. (15) Trolox slightly decreased dC, dG, and dT. Trolox is another water-soluble αtocopherol analog, substituting a hydrocarbon chain for a carboxy group.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…(14) Recently, we reported that α-tocopherol phosphate induces the UV reaction of nucleosides, especially dT, generating 5,6dihydrothymidine as the major product. (15) Trolox slightly decreased dC, dG, and dT. Trolox is another water-soluble αtocopherol analog, substituting a hydrocarbon chain for a carboxy group.…”
Section: Resultsmentioning
confidence: 97%
“…(16) Reportedly, Trolox induces the reaction of nucleosides by UV irradiation, although 5,6-dihydrothymidine is not generated. (15) Tryptophan reduced the dT concentration. It has been reported that tryptophan reacts with thymine to generate photoadducts by UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations